Correlation between Heredity Factor and Menarcheal Age among Adolescent Aged 9â15 Years Old - Khotimah, Nurul; Fadil, R.M. Ryadi; Tansah, Haryono (Althea Medical Journal, 2017)
Background: Menarche is a sign of maturity of the female reproductive function. It is influenced by many factors, such as heredity, general health status, nutrition, and socioeconomic status. The purpose of this study is to determine the correlation of heredity and menarcheal age.Methods:This study was a cross-sectional analytic study conducted from SeptemberâOctober 2014 in Bandung using a multi-stage sampling technique and it wasÂ  conducted in twelve elementary schools and junior high schools. A total of 123 subjects were included in this study. The instrument of this study was questionnaire containing menarcheal age of subject, older sister, biological mother, and maternal grandmother. The data were analyzed using Spearman correlation and linear regression test with the level of significance was determined at p<0.05. Results: Among 123 data, the majority of subjects had experienced menarche at the age of 11 (39%) and 12 years (36.6%) with an average of 11.46 years old. Based on the Spearman correlation and multiple linear regression tests, there was a correlation between heredity and menarcheal age. (P=0.00).Conclusions: There is a correlation between heredity and menarcheal age, with the highest correlation is between subjectâs and older sisterâs menarcheal age. Â DOI:Â 10.15850/amj.v4n2.1081